Concept of a Fuel Injector Control System Based on Electric Current Signals in OBD - Adrian POŁANIECKI; Kinga SZOST; Jędrzej MĄCZAK (Engineering Transactions, 2025)
This work presents a concept for controlling the injectors of internal combustion engines. It is possible to observe electric current signals with high repeatability on the coil of fuel injectors. Mechanical changes observed in these signals indicate the presence of certain anomalies, allowing for fault detection. A precise analysis of characteristic points in the signal enables diagnosing the injector’s condition in the next control loop.